Prevalence and Biofilm-forming Potentials of Bacterial Uropathogens Among Primary School Pupils in Yola North, Adamawa State - Abaka, Abdulazeez Mumsiri; Dahiru, Mubarak Muhammad; Ya'u, Ibrahim; Abdulllahi, Tukur Baba (Biology, Medicine, & Natural Product Chemistry, 2023)
This investigation aimed to determine the prevalence and biofilm-forming potentials of bacterial uropathogenic among primary school pupils in Yola North, Adamawa State. A total of 120 clean mid-stream urine samples were collected from apparently healthy children to determine the antimicrobial susceptibility of the isolated pathogen by the Kirby and Bauer disc diffusion method while the biofilm-forming potential by the standard methods. The result showed 26 % of the samples had significant bacteria growth with the Gram-negative as the highest. The infectivity pattern among the age group showed 8-10 had the highest infectivity percentage (35%) followed by 5-7 and 11-13 with 22.5% and 20% respectively. Six bacteria pathogens were isolated which are E. coli (41.9%) which is the most prevalent isolate followed by Staphylococcus aureus (29.0%), Pseudomonas sp. (9.7%), Klebsiella sp. (9.7%), Enterobacter sp. (6.5%), Proteus sp. (3.3%). The antibiotic sensitivity test showed an alarming resistance level to nearly all the tested antibiotics showing multi-drug resistant strains. The Biofilm-forming potentials depict E. coli with the strongest potential followed by S. aureus. A high occurrence of asymptomatic UTIs and antimicrobial resistance observed poses a public health concern. Thus, routine diagnostic exercise is recommended for early detection and prompt treatment of the pathogens.